SR9883 is a novel small-molecule enhancer of α4β2* nicotinic acetylcholine receptor signaling that decreases intravenous nicotine self-administration in rats - Braunscheidel, Kevin M.; Voren, George; Fowler, Christie D.; Lu, Qun; Kuryatov, Alexander; Cameron, Michael D.; Ibañez-Tallon, Ines; Lindstrom, Jon M.; Kamenecka, Theodore M.; Kenny, Paul J. (Frontiers in Molecular Neuroscience, 2024)
BackgroundMost smokers attempting to quit will quickly relapse to tobacco use even when treated with the most efficacious smoking cessation agents currently available. This highlights the need to develop effective new smoking cessation medications. Evidence suggests that positive allosteric modulators (PAM) and other enhancers of nicotinic acetylcholine receptor (nAChR) signaling could have therapeutic utility as smoking cessation agents.Methods3-[3-(3-pyridyl)-1,2,4-oxadiazol-5-yl]benzonitrile (NS9283) was used as a starting point for medical chemistry efforts to develop novel small molecule enhancers of α4β2* nAChR stoichiometries containing a low-affinity agonist binding site at the interface of α4/α4 and α4/α5 subunits.ResultsThe NS9283 derivative SR9883 enhanced the effect of nicotine on α4β2* nAChR stoichiometries containing low-affinity agonist binding sites, with EC50 values from 0.2–0.4 μM. SR9883 had no effect on α3β2* or α3β4* nAChRs. SR9883 was bioavailable after intravenous (1 mg kg−1) and oral (10–20 mg kg−1) administration and penetrated into the brain. When administered alone, SR9883 (5–10 mg kg−1) had no effect on locomotor activity or intracranial self-stimulation (ICSS) thresholds in mice. When co-administered with nicotine, SR9883 enhanced locomotor suppression and elevations of ICSS thresholds induced by nicotine. SR9883 (5 and 10 mg kg−1) decreased responding for intravenous nicotine infusions (0.03 mg kg−1 per infusion) but had no effect on responding for food rewards in rats.ConclusionsThese data suggest that SR9883 is useful for investigating behavioral processes regulated by certain α4β2* nAChR stoichiometries. SR9883 and related compounds with favorable drug-like physiochemical and pharmacological properties hold promise as novel treatments of tobacco use disorder.